Predicting sensory perceptions of thickened solutions based on rheological analysis - He, Qi; Hort, Joanne; Wolf, Bettina (Elsevier, 2016)
The sensory perceptions of sweetened, flavoured and thickened solutions prepared from xanthan, dextran, sucrose and banana flavour were evaluated and correlated to rheological parameters. The primary aim of this research was to evaluate the relevance of viscosity measured at low shear or at high shear for predicting sensory perceptions. Additionally considered were extensional viscosity estimated from filament thinning experiments and complex shear viscosity. The design of experiments included two groups of 5 samples matched at low shear rate and high shear rate, respectively. Mouthfeel perceptions were well correlated to low shear viscosity, however, including high shear viscosity or extensional viscosity as an additional model parameter improved the predictive quality of the models for thickness, stickiness and mouth coating. Stickiness and mouth coating were better correlated to extensional viscosity than low shear viscosity, although a model including both parameters predicted stickiness and mouth coating best. The complex viscosity at 100 rad/s was also highly correlated to the perception of thickness. Since correlations were not improved over steady shear parameters, complex viscosity was not considered in models based on more than one rheological parameter. Flavour was also scored during sensory evaluation and sweetness and overall flavour were highly correlated. The results of this study have highlighted that there is no single rheological parameter that will ultimately correlate to a range of mouthfeel perceptions. For certain mouth feel perceptions a model comprising shear and extensional rheological parameters will have higher predictive power than a model solely based on shear rheological parameters.